K.H. Ahmad Dahlan Sebagai Tokoh Pembaharu - M Dahlan M (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2014)
Ahmad Dahlan is one of the reformer figure in Moslem of Indonesia who we couldn’t deny him. Ahmad Dahlan’s movement was very incredible to redesign the consciousness of reformer in our societies which we could felt it now. Ahmad Dahlan in his revolution movement had planned to made direction of Mecca’s to be corrected, to fixed Bid’ah and Khurafat, his development in social side and education in an organization had called Muhammadiyah. Muhammadiyah had given so much incredible benefits to development of Indonesia societies, especially the Moslem of Indonesia.